Potential of Andaliman Fruit Extract (Zanthoxylum acanthopodium) As A Natural Feed Additive on the Income Over Feed and Chick Cost (IOFCC) of Broiler Chickens - Santi, Melia Afnida; Nurhayati, Nurhayati; Suryani, Heni; Maradon, Gusma Gama; Sinaga, Desi Maria; Pertiwi, Vindo Rossy; Elvan, Elvan; Karima, Fadhila Nurul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: The increase in feed and DOC costs has become the main factor squeezing the profit margins of broiler chicken businesses. Various phytogenic feed additives have been reported to improve production performance, but most studies still focus on biological parameters such as weight gain and feed conversion. Studies evaluating its impact on economic indicators, particularly Income Over Feed and Chick Cost (IOFCC), are still limited, especially regarding the use of local plants such as andaliman (Zanthoxylum acanthopodium). Objective: This study aims to analyze the effect of adding Andaliman extract in the feed on the IOFCC value of broiler chickens as an indicator of economic production performance. Method: The research was conducted over 28 days using a completely randomized design (CRD) with five treatments and four replications: P0 (without extract), P1 (0.5%), P2 (0.75%), P3 (1%), and P4 (1.25%). The observed parameters include feed price, ration cost, final weight, selling price, income, and IOFCC value. Data were analyzed descriptively and quantitatively based on actual economic evaluation. Results: The addition of Sichuan pepper extract increased final weight, income, and IOFC value. The highest IOFCC value was obtained in P4 at Rp 23,805.65/head, followed by P3 at Rp 22,994.75/head, while the lowest was in P2 at Rp 14,575.50/head. The 1–1.25% level shows the best economic efficiency, which is suspected to be related to the activity of bioactive compounds such as flavonoids and terpenoids. Conclusion: Andaliman extract at levels of 1–1.25% has the potential to serve as a natural feed additive based on local resources to enhance the efficiency and sustainability of broiler chicken farming.